Voltage Stability Assessment of Dubai Power Grid Using a Detailed Load Model - Al Disi, Salha Ali (2013)
A Master of Science thesis in Electrical Engineering by Salha Ali Al Disi entitled, "Voltage Stability Assessment of Dubai Power Grid Using a Detailed Load Model," submitted in June 2013. Thesis advisor is Dr. Ahmed Osman and Co-advisor is Dr. Awad Ibrahim Al-Baraasi. Available are both soft and hard copies of the thesis.